Anti-dementia medications – fighting a losing battle? - Micov, Ana; Pecikoza, Uros (Archives of Pharmacy, 2020)
Alzheimer’s disease (AD), the most common cause of dementia, is a growing health, social and economic problem due to the increasing number of sufferers, limited efficacy of available treatment options and high total healthcare costs. It is clinically characterized by cognitive and behavioural impairments, both of which need to be treated appropriately to improve quality of life for patients and their caregivers. Currently available anti-dementia medications provide only modest and transient cognitive benefits. Donepezil, rivastigmine and galantamine (cholinesterase inhibitors) are indicated for the symptomatic treatment of mild to moderately severe AD, while memantine (antagonist of glutamatergic NMDA receptors) is recommended for moderate-to-severe AD. A special focus on behavioral symptoms (e.g. anxiety, depression, aggression) management is required as they cause great suffering in patients/caregivers. The use of medications that can impair cognitive function, such as anticholinergic drugs, should be avoided in patients with dementia. Additionally, interventions that might have the potential to delay or prevent dementia onset in some subjects are focused on minimizing modifiable risk factors (hypertension, diabetes, depression) and maximizing protective factors (higher level of education, physical activity, healthy diet, leisure and social activities). The treatment of AD remains a challenge.